Rethinking Material Religion in the East: Orientalism and Religious Material Culture in Contemporary Western Academia - Wang, Xing (Religions, 2018)
This paper reviews the historical development of the modern discourse of Orientalism and the emergence of material culture as a self-reflexive theoretical transition in the West. Further, it investigates new types of Orientalism in the study of religious material culture. The traditional Orientalist approach to understanding foreign cultures has been abandoned in Western academia for decades owing to its moral judgment and lack of neutrality. However, an implicit form of Orientalism still exists in contemporary Western academia. Material culture appeared as a new trend in understanding the world as not solely dominated by human beings but also transformed by material objects. Religious material culture, far from explaining the reality of religious phenomena in different cultures, constructs new realities to solve problems in Western intellectual discourse. This is the case with the study of Chinese religions and material life.